Length impairments of the axon initial segment in rodent models of attention-deficit hyperactivity disorder and autism spectrum disorder. (February 2022) - Usui, Noriyoshi; Tian, Xiaoye; Harigai, Wakana; Togawa, Shogo; Utsunomiya, Ryo; Doi, Tomomi; Miyoshi, Ko; Shinoda, Koh; Tanaka, Junya; Shimada, Shoichi; Katayama, Taiichi; Yoshimura, Takeshi
Abstract: The axon initial segment (AIS) is a structural neuronal compartment of the proximal axon that plays key roles in sodium channel clustering, action potential initiation, and signal propagation of neuronal outputs. Mutations in constitutive genes of the AIS, such as ANK3, have been identified in patients with neurodevelopmental disorders. Nevertheless, morphological changes in the AIS in neurodevelopmental disorders have not been characterized. In this study, we investigated the length of the AIS in rodent models of attention-deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). We observed abnormalities in AIS length in both animal models. In ADHD model rodents, we observed shorter AIS length in layer 2/3 (L2/3) neurons of the medial prefrontal cortex (mPFC) and primary somatosensory barrel field (S1BF). Further, we observed shorter AIS length in S1BF L5 neurons. In ASD model mice, we observed shorter AIS length in L2/3 and L5 neurons of the S1BF. These results suggest that impairments in AIS length are common phenomena in neurodevelopmental disorders such as ADHD and ASD and may be conserved across species. Our findings provide novel insight into the potential contribution of the AIS to the pathophysiology and pathogenesis of neurodevelopmental disorders. Highlights: In mouse and rat models of ADHD, mPFC & S1BF neurons have shorter AIS lengths. In ASD model mice, S1BF neurons have shorter AIS lengths. A disorder-specific AIS phenotype may be conserved across species. AIS abnormalities in S1BF neurons are common phenotypes in ADHD & ASD.